Ibrah Mau’idzah melalui Cerita Islami - Grace Wizratul Kamilah; Fayruzah El-Faradis (Fakta: Jurnal Pendidikan Agama Islam, 2021)
Ibrah Mau’idzah through Islamic stories is one of the methods that can be used and good influenced in internalizing islamic values for children. Ibrah Mau’idzah itself is a way that takes the essence of the event, whether it is a self-experience or someone else. Then, by the admonitions and warnings of good and bad something contained in the event or story. And this study aims to demonstrate what islamic religious values are internalized, as well as to describe the process of internalizing islamic values for children in the teacher’s family using these methods and media. This data source is a sample taken from six families whose parents were teachers and had children of approximately 3-12 years old. this research used  qualitative approach, and data sources through observation and interview. The result of this study is the islamic values internalized toward children that constitute the value of worship and moral values. Ibrah Mau’idzah as a method used to internalize the islamic religious values has positive effect on children and has proven to be effective for used. That showed from children that have ability in carrying out prayer, fasting, honoring parents and so on.